ANALYSIS OF HOMOPHONE PHYRAMID LANGUAGE IN THE LANI TRIBE” PAPUA PEGUNUNGAN - Kogoya, Napius; Halitopo, Manase (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study analyzes the phenomenon of homophone pyramid language in the Lani Tribe of Papua Pegunungan, revealing that homophones in the Lani language are not merely linguistic coincidences but embody unique phonological patterns and semantic variations deeply connected to the tribe’s cultural and environmental context. Through descriptive linguistic analysis and field-based data collection, the study identifies several instances of lexical homophony such as tu (“door” / “road”), mayu (“rain” / “salt”), nengge (“eat” / “drink”), ngilu (“cucumber” / “snack”), eyo (“tree” / “barren”), kolee (“leader” / “older man”), abila (“pregnant” / “fat man”), and anuka (“head” / “Anuak tribe”). These examples demonstrate that meaning in the Lani language is primarily determined by contextual cues and pragmatic usage. The findings suggest that homophones in Lani function as linguistic features and cultural expressions that reflect the tribe’s perception of nature, community roles, and social identity. This research contributes to a broader understanding of Papuan linguistics and underscores the importance of preserving indigenous languages as repositories of cultural knowledge and intellectual heritage.